(untitled) (Journal of Educational Sciences, 2017)
The article analyzes and compares the characteristics and state of the art therapy and art-pedagogical services in the countries of near and far abroad and in Kazakhstan. Тhe use of elements of art therapy in prevention contributes to the strengthening of protective factors in relation to possible involvement in a negative environment, including suicidal aims. In this regard, the analysis and synthesis of data about foreign art therapy and art-pedagogical services, as well as questionnaire-based survey and analysis of sites summarizes the status of these services in the Republic of Kazakhstan on the example of Almaty city. In the result, the conclusion o under representation of this sector psychological service in our country. Art therapy in contrast to art teaching were more strongly represented in the market of educational and psychological services, but due to certain circumstances (high costs, weak advertising, etc.) the youth does not use them. In the Republic of Kazakhstan of art therapy and art-pedagogical services are in the early stages. The belief is based on summation of the experience of existing centres and services (practitioners of the art pedagogy and art therapy with various categories of people), what specific goals, and in particular, in the field of prevention of suicidal perspectives art therapists and art teachers do not put; in most cases they solved the problem of overcoming the communicative Buryanov, maladjustment, children with special educational needs. The article represents intermediate results of the grant of the Ministry of education and science of the Republic of Kazakhstan “The Art pedagogic and art therapy for the prevention of suicidal behavior of youth in Kazakhstan: development of scientific bases and practical technologies” in the aspect of testing developed by the authors of the art technology.